Pemberdayaan Masyarakat Melalui Pengolahan Buah Nipah (Nypa Fruticans, Wurmb) Menjadi Berbagai Produk Olahan Dan Pembentukan Sentra Industri Kecil Di Kecamatan Langsa Timur Kota Langsa - Juanda, Boy Riza; Risyad, Syukri; Hanisah, Hanisah (Dewan Pimpinan Daerah (DPD) Forum Dosen Indonesia JATIM, 2018)
This program is designed to answer the problem of unavailability of potential human resources in processingand utilizing the potential of local raw materials as a business that can be developed to increase the income of localfarmers. With the implementation of this pioner program, the training is designed, Establishment of Joint Business Group